A new species of Thelepus (Annelida, Terebelliformia) from Banc d’Arguin, Mauritania, and its associated scaleworm Lepidonotus hupferi Augener, 1918 (Annelida, Polynoidae) - Lavesque, Nicolas; Bonifácio, Paulo; Gouillieux, Benoit; Daffe, Guillemine; Daramy, Flore; Hutchings, Pat (Zootaxa, 2026)
To date, only one species of the terebellid polychaete genus Thelepus Leuckart, 1849 has been described from Africa: T. pequenianus Augener, 1918. During a 2024 biodiversity survey in Arguin National Park (Mauritania), we discovered a second African species that we describe as Thelepus arguinensis sp. nov. It is characterised by notopodia restricted to only 20–35% of the body, three pairs of branchiae, each with numerous filaments, dorsal branchial gap absent, and thoracic uncini lacking a prow. Phylogenetic analyses of mitochondrial 16S and COI sequences confirm its distinctiveness from all congeners with available data. We also redescribe the polynoid Lepidonotus hupferi Augener, 1918 found sharing the tubes of some specimens of T. arguinensis sp. nov. and provide the first molecular data for the species, while extending its known distribution to Mauritania. This study documents a previously unreported facultative, likely commensalistic, association between the two species, highlighting both the underestimated diversity of West African polychaetes and the limited knowledge on the terebellid–polynoid relationships in the region.